Generational Ideology Tables of the Spanish Population - Cristina Aybar; Virgilio Pérez; Jose M. Pavía (Scientific Data)
Abstract Studying ideological preferences is essential for understanding the social and political changes a society undergoes over time. Generational ideology tables provide a structured framework to analyze ideological shifts within and across generations, offering valuable insights into societal evolution and political behavior. This paper introduces the Spanish Cohort Ideology Database (SCID), detailing the data sources and methodology used for its construction. By leveraging more than five million individual observations (which expand to over 100 million when employing double 5 × 5 moving windows) from over 1,800 surveys conducted since 1977 by the Spanish official center for sociological research (CIS), we construct 1,554 period and cohort ideology tables, including breakdowns by gender, education level, gender and education level, and region. SCID comprises age-year and age-generation tables with mean values, sample sizes, and variances, enabling the analysis of the dispersion/polarization of ideological self-placement. This work facilitates the analysis of social and political change processes from a cross-section and longitudinal perspective, creating a unique database that could also be developed in other countries, thereby enabling international comparative studies.